2023
DOI: 10.3390/buildings13102558
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Seismic Behavior of Demountable Joints Consisting of Reinforced Concrete Columns and Steel Beams

Jianguo Cai,
Zhong Deng,
Wei Li

Abstract: In this study, three new types of demountable connections, consisting of reinforced concrete columns and steel beams, are proposed, and their seismic performance is investigated through the use of cyclic loading tests. The test results reveal that these three demountable RCS joints show good seismic performance, in which the ductility coefficients of specimens RCS-1 and RCS-2 are improved by 69% and 109%, respectively, compared with the reference group of RCS-0 specimens. Various parameters, such as the beam f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Plastic deformation and sufficient joint ductility were found in the experiments of Zhang et al [11] on the steel beam-column connection between a cantilever beam and a normal I-beam composing of a flange plate, a web plate, and highstrength bolts in accordance with standard specifications. Cai et al [12] proposed three new detachable connection structures composed of reinforced concrete columns and steel beams, and the final results found that the new detachable RCS bolt connection is not only far better than the ordinary joints in terms of seismic performance, but also in the application of detachable structures in construction. The authors Wang et al [13] have developed a prefabricated bolted steel member end embedded concrete beam-column connection to address the limitations of current dry-joined prefabricated joints.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic deformation and sufficient joint ductility were found in the experiments of Zhang et al [11] on the steel beam-column connection between a cantilever beam and a normal I-beam composing of a flange plate, a web plate, and highstrength bolts in accordance with standard specifications. Cai et al [12] proposed three new detachable connection structures composed of reinforced concrete columns and steel beams, and the final results found that the new detachable RCS bolt connection is not only far better than the ordinary joints in terms of seismic performance, but also in the application of detachable structures in construction. The authors Wang et al [13] have developed a prefabricated bolted steel member end embedded concrete beam-column connection to address the limitations of current dry-joined prefabricated joints.…”
Section: Introductionmentioning
confidence: 99%